2011
DOI: 10.1186/1471-2369-12-35
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy activities in chronic kidney disease and end-stage renal disease patients: a systematic literature review

Abstract: BackgroundChronic kidney disease (CKD) and end-stage renal disease (ESRD) represent worldwide health problems with an epidemic extent. Therefore, attention must be given to the optimisation of patient care, as gaps in the care of CKD and ESRD patients are well documented. As part of a multidisciplinary patient care strategy, clinical pharmacy services have led to improvements in patient care. The purpose of this study was to summarise the available evidence regarding the role and impact of clinical pharmacy se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 31 publications
3
63
2
4
Order By: Relevance
“…Similar results have previously been reported in other studies [1,2,5,13,19]. Thus, information is available and treatment guidelines give advice for the proper treatment of these patients [17,20].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have previously been reported in other studies [1,2,5,13,19]. Thus, information is available and treatment guidelines give advice for the proper treatment of these patients [17,20].…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted at five Norwegian hospitals in 2006 showed that 62 % of patients with RI had DRPs linked to renal risk drugs [1]. Several studies have shown that medication reviews conducted by clinical pharmacists in multidisciplinary teams in hospitals contribute to a reduction in DRPs [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a lot of interest in anemia outcomes related to CKD utilizing team-based interventions [28,29,30]. A meta-analysis [29] reviewed the types of pharmacist interventions in the management of patients with CKD.…”
Section: Evidence Supporting Improved Cardiovascular and Kidney Outcomentioning
confidence: 99%
“…pharmacist involvement at healthcare centers proved dedicated role in clinical time and in minimizing medication related discrepancies and clinical pharmacist involvement proved gradual decline in medication error, proper discharge record regarding medications and understanding about their medication in outpatients. They proved their dedicated role in critical units by providing quality of services 4 chronic disease [5][6][7] like diabetes and life threatening diseases [8][9] and by built up relationship with trust 10 to reduce drug cost 11 by facing challenging task 12 and by reducing their duration of stay in hospital 13 and by collaborative role with physician based on scientific evidence and pharmacy care planes [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%